Identity – a Brief Humanistic Perspective - Sośnicka, Joanna (Facets of Managing in Cross-Cultural Diversity, 2021)
Today identity is ‘the loudest talk in town’, the burning issue on everybody’s mind and tongue. Normally, we tend to notice things and put them into the focus of our scrutiny and contemplation only when they vanish, go bust, start to behave oddly or otherwise let us down (Bauman 2004: 16–17).Does the concept of identity find itself in a similar situation? Any extensive analysis undoubtedly blurs the concept, and interdisciplinary approaches do not help with grasping the essence of identity (if that is possible at all). The objective of this article is not to create another definition (we have enough already); instead, by making use of the richness of humanistic thought, the goal is to draw attention to certain dimensions and aspects of realizing identity, which are currently, in the author’s opinion, worth considering. Personal identity is not created in a vacuum – one’s environment and social reality have a great impact on them. The chapter addresses these influences with particular attention to selected elements.This article was financed by the EU-CAB project implemented under the Erasmus + Strategic Partnership in the higher education sector and co-financed by the European Union